Jihad in Paradise - Muhamad Ali (International Institute of Islamic Thought, 2006)
Jihad in Paradise explores cultural and religious interaction in Singapore and compares this with the intolerant radical Islamism threatening the country and Southeast Asia in general. Millard, a senior journalist who first worked on East Asia and then Southeast Asia, artfully conveys his descriptive yet analytical narrative of how Southeast Asia underwent radical change due, in large part, to the influence of global and regional terrorism. Meanwhile, Singapore has yet to move forward by allowing greater political freedom and developing mutual dialogue and cooperation between its different religious communities. The Malay minority must also adjust itself to such pragmatic economic and political climates. Singapore’s future depends on how well it manages multicultural diversity and balances its economic progress and political democracy. The book is divided into six chapters. In his introduction, Millard observes how Singapore and Southeast Asia were generally prosperous and peaceful until the Asian financial crisis of 1997-98, 9/11, and the 2002 Bali bombings. He realizes that his book is not an “inside story,” for he regards himself as only journalist who is deeply interested in human realities and their regional and global dimensions ...